The association between sexual dysfunction and metabolic syndrome among Turkish postmenopausal women - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2019)
Objective: The aim of this study is to determine the association between sexual dysfunction and metabolic syndrome (MS) among Turkish postmenopausal women Methods: In total, 290 postmenopausal women between the ages of 50 and 70 years and 265 premenopausal women between the ages of 30 and 49 years who applied to Menopause and Gynecology Clinics at Marmara University-affiliated Pendik Education and Research Hospital, Istanbul, Turkey were included in this prospective survey. Sexual function was assessed using the Female Sexual Function Index (FSFI). A FSFI total score of Results: Sexual dysfunction prevalence among postmenopausal women was 64.6% in relation to 42.1% in premenopausal women (p = 0.001). MS prevalence was 13.5% among premenopausal women and 15.5% among postmenopausal women (p = 0.57). The total FSFI score and each score in the desire, arousal, lubrication, orgasm, satisfaction, and dyspareunia domains of the FSFI did not differ between premenopausal and postmenopausal women, regarding the MS status. In the premenopausal group, 45.7% of women without MS and 37% of women with MS had lower sexual dysfunction (p = 0.40); whereas in the postmenopausal group, 62.2% of women without MS and 77.4% of women with MS had lower sexual function (p = 0.22). Conclusion: In our study population, the rate of sexual dysfunction increased in postmenopausal women in contrast to premenopausal women. The MS status did not make a difference in terms of sexual dysfunction either in premenopausal or postmenopausal women. Since our survey was conducted in a tertiary medical center which gave medical care service to women from middle and low socioeconomic classes, our results should be confirmed by a large multicenter survey enrolling women from all different socioeconomic classes.
Keywords: Female Sexual Function Index; menopause; metabolic syndrome; sexual dysfunction; MORBIDLY OBESE WOMEN; CARDIOVASCULAR-DISEASE; UNITED-STATES; NITRIC-OXIDE; RISK-FACTORS; PREVALENCE; HEALTH; DEFINITIONS; MENOPAUSE; PROFILE